Tumorigenesis related to retroviral infections - Braoudaki, Maria; Tzortzatou-Stathopoulou, Fotini (The Journal of Infection in Developing Countries, 2011)
Retroviral infections are considered important risk factors for cancer development in humans since approximately 15-20% of cancer worldwide is caused by an infectious agent. This report discusses the most established oncogenic retroviruses, including human immunodeficiency virus (HIV), human T-cell leukemia virus (HTLV-1 and -2), Rous sarcoma virus (RSV), Abelson murine leukemia virus (A-MuLV), Moloney murine leukemia virus (M-MuLV), murine mammary tumor virus (MMTV), bovine leukemia virus, (BLV), Jaagsiekte sheep retrovirus (JSRV), and Friend spleen focus-forming virus (SFFV). The role of retroviruses as inducers of carcinogenesis, the mechanisms underlying oncogenic transformation, and the routes of transmission of several cancer-related retroviral infections are also described. Finally, the impact of cancer-related retroviral infections in the developing world is addressed. This review is an update of carcinogenesis caused by retroviral infections.